I need help With what the answer is
![I need help With what the answer is class=](https://us-static.z-dn.net/files/d88/d3b849cef53f68f48bf2bd95930489a7.png)
Answer:
OPTION C: y = 2x² + 1
Step-by-step explanation:
To identify the function substitute the values of 'x' and 'y' and compare LHS and RHS.
OPTION A: y = -(5x + 1)
When x = -2, y = 9
Therefore, LHS = 9
RHS = -(5(-2) + 1) = -(-10 + 1) = 9
So, LHS = RHS.
Now, we check for the second pair. i.e., (x, y) = (-1, 3)
LHS = 3
RHS = -(-5 + 1) = -(-4) = 4
LHS [tex]$ \ne $[/tex] RHS
So, this option is eliminated.
OPTION B: y = - 4x + 1
Like OPTION A, substitute x = -2 and y = 9.
LHS = 9
RHS = - 4(-2) + 1 = 9
LHS = RHS
Now for the second pair: (-1, 3)
LHS = 3
RHS = -4(-1) + 1 = 4 + 1 = 5
We see LHS [tex]$ \ne $[/tex] RHS.
So, this option is eliminated as well.
OPTION C: y = 2x² + 1
Substituting the first pair: (-2, 9)
LHS = 9
RHS = 2(4) + 1 = 9
So, LHS = RHS
Now For the second pair: (-1, 3)
We have LHS = 3
RHS = 2(1) + 1 = 3
LHS = RHS.
The third pair: (0, 1)
LHS = 1
RHS = 2(0) + 1 = 1
For the pair: (1, 3)
LHS = 3
RHS = 2(1) + 1 = 3
Again, LHS = RHS
For the pair: (2, 9)
LHS = 9
RHS = 2(4) + 1 = 9
Since, for all the pairs we have LHS and RHS equal, we con conclude that this is the correct representation of our function.
Similarly, substitute OPTION D. The option can be eliminated in the second pair itself.
So, the answer is OPTION C.